2019
DOI: 10.1155/2019/5653212
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 2 Interacting Protein-1 Suppresses Glioma Cell Proliferation via Regulating the AKT/GSK3β/β-Catenin Pathway

Abstract: Objective. Casein kinase 2 interacting protein-1 (CKIP-1) has exhibited multiple functions in regulating cell proliferation, apoptosis, differentiation, and cytoskeleton. CKIP-1 also plays an important role as a critical regulator in tumorigenesis. The aim of this study is to further examine the function of CKIP-1 in glioma cells. Methods. The expression level of CKIP-1 protein was determined in gliomas tissues and cell lines by immunohistochemistry stain and western blotting while the association of CKIP-1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…2 d), meaning si-HOXA-AS2 was successfully transfected into U87 and U251 cells. CCK-8, BrdU and flow cytometry are commonly used to evaluate the proliferation and apoptosis of cancer cells [ 27 , 28 ]. Our CCK-8 assay outcome indicated that compared with the blank group, silencing HOXA-AS2 inhibited cell viability after U87 and U251 cells were transfected with si-HOXA-AS2 for 48 and 72 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 d), meaning si-HOXA-AS2 was successfully transfected into U87 and U251 cells. CCK-8, BrdU and flow cytometry are commonly used to evaluate the proliferation and apoptosis of cancer cells [ 27 , 28 ]. Our CCK-8 assay outcome indicated that compared with the blank group, silencing HOXA-AS2 inhibited cell viability after U87 and U251 cells were transfected with si-HOXA-AS2 for 48 and 72 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CCK-8 assay, BrdU assay and flow cytometry are commonly used to study the proliferation and apoptosis of cancer cells [ 27 , 28 ]. Cell adhesion assay is also performed to assess tumor development [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our qRT-PCR analysis showed that HOXA-AS2 silencing signi cantly reduced HOXA-AS2 expression by 70% compared to the blank group ( Figure 2D), meaning si-HOXA-AS2 was successfully transfected into U87 and U251 cells. CCK-8, BrdU and ow cytometry are commonly used to evaluate the proliferation and apoptosis of cancer cells [27,28]. Our CCK-8 assay outcome indicated that compared with the blank group, silencing HOXA-AS2 inhibited cell viability after U87 and U251 cells were transfected with si-HOXA-AS2 for 48 and 72 hours ( Figure 2E).…”
Section: Effects Of Si-hoxa-as2 On Glioblastoma Samplesmentioning
confidence: 87%
“…CCK-8 assay, BrdU assay and ow cytometry are commonly used to study the proliferation and apoptosis of cancer cells [27,28]. Cell adhesion assay is also performed to assess tumor development [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…4 Currently, research suggests that the CKIP-1 gene might play an important role in the occurrence and development of several malignancies. 59 However, the specific role of CKIP-1 in GC remains unclear. Previous research by the current authors demonstrated that the CKIP-1 gene was related to GC cell differentiation and involved in the proliferation, migration and invasion of GC, acting as a tumour suppressor gene.…”
Section: Introductionmentioning
confidence: 99%